Escherichia coli Nissle 1917 restores epithelial permeability alterations induced by irritable bowel syndrome mediators. Issue 8 (28th June 2018) - Barbaro, M. R.; Fuschi, D.; Cremon, C.; Carapelle, M.; Dino, P.; Marcellini, M. M.; Dothel, G.; De Ponti, F.; Stanghellini, V.; Barbara, G.
Abstract: Background: Intestinal permeability is altered in a subgroup of irritable bowel syndrome (IBS) patients and may contribute to symptom development. The aim of this study was to evaluate the in vitro effect of the probiotic Escherichia coli Nissle 1917 (EcN) on Caco‐2 permeability alterations induced by mediators released by IBS mucosal biopsies compared to asymptomatic controls (AC). Methods: Caco‐2 cells were used as an in vitro model of intestinal permeability. Seven AC and 28 well‐phenotyped IBS (9 IBS‐D, 8 IBS‐C, and 11 IBS‐M) patients were enrolled. Mucosal mediators spontaneously released (SUP) by IBS and AC biopsies were collected. Two concentrations of EcN (10 8 and 10 6 ) were applied to Caco‐2 with or without SUP or SLIGRL (a protease‐activated receptor‐2 activating peptide), tumor necrosis factor‐α, and interferon‐γ. Paracellular permeability was assessed by evaluating the flow of sulfonic‐acid conjugated to fluorescein through Caco‐2 monolayer. Key Results: EcN 10 8 significantly reinforced Caco‐2 monolayer compared to cells incubated with medium alone. IBS SUP induced a significant increase in paracellular permeability compared to AC SUP, independently of IBS bowel habit. EcN 10 8 induced a significant recovery of permeability rate compared to IBS SUP. Permeability increase induced by IBS SUP significantly correlated with severity and frequency of abdominal pain and abdominal distension. The co‐incubation of EcN and IBS SUP abolished the above significant correlations. Conclusions and Inferences: EcN reinforces the integrity of Caco‐2 monolayer and reverts the increase of permeability induced by mediators released by IBS biopsies. Future studies should investigate EcN therapeutic potentials in IBS. Abstract : The intestinal epithelial barrier is altered in subsets of irritable bowel syndrome (IBS) patients and may contribute to abdominal pain. Probiotics are among the best‐known approaches to restore epithelial barrier dysfunction. This property of probiotics may be beneficial to subsets of IBS patients. We report that EcN reinforced Caco‐2 monolayer and reverted permeability alterations induced by mediators spontaneously released by IBS biopsies, partly through protease and cytokine pathways. Our data pave the way to future investigation on the application of EcN in IBS.